2023
DOI: 10.1017/s0267190523000016
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Body Problem: The effects of foreign language anxiety, enjoyment, and boredom on academic achievement

Jean-Marc Dewaele,
Elouise Botes,
Rachid Meftah

Abstract: This study is part of a growing wave of interest in foreign language (FL) learners’ emotions, their sources, and their effects. Previous studies have confirmed that there is a clear relationship between the emotions of foreign language enjoyment (FLE), foreign language classroom anxiety (FLCA), foreign language boredom (FLB), and foreign language performance. However, the relative importance of each emotion as a predictor of FL performance has yet to be examined, and as different teaching and learning strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 50 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…In addition, the study revealed a significant negative relationship between FLLB and FLE, indicating that students who do not enjoy learning their foreign language are more likely to get bored. This result is not surprising, confirming previous studies (Dewaele, Albakistani, et al, 2022;Dewaele, Botes, & Greiff, 2023;Dewaele, Botes, & Meftah, 2023;Wang & Li, 2022;Zhao & Wang, 2023). The positive correlation between boredom and enjoyment provides additional support for the validation of the "undo hypothesis" proposed by the BBT (Fredrickson, 2004(Fredrickson, , p. 1371.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, the study revealed a significant negative relationship between FLLB and FLE, indicating that students who do not enjoy learning their foreign language are more likely to get bored. This result is not surprising, confirming previous studies (Dewaele, Albakistani, et al, 2022;Dewaele, Botes, & Greiff, 2023;Dewaele, Botes, & Meftah, 2023;Wang & Li, 2022;Zhao & Wang, 2023). The positive correlation between boredom and enjoyment provides additional support for the validation of the "undo hypothesis" proposed by the BBT (Fredrickson, 2004(Fredrickson, , p. 1371.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, learners who had higher levels of FLCA experienced greater levels of boredom. The positive relationships between FLLB, FLE, and FLCA confirm the results reported by Dewaele, Botes, and Meftah (2023), as well as , who found a significant positive correlation between FLCA and FLLB among EFL learners in Morocco.…”
Section: Foreign Language Learning Boredomsupporting
confidence: 90%
See 1 more Smart Citation
“…The measurement instrument for enjoyment in foreign languages has evolved from the original proposal of the Foreign Language Enjoyment Scale by Dewaele and MacIntyre in 2014 [cited by Dewaele et al (2023)], which consisted of 21 items. In 2021, Botes et al (2022) developed a shortened version, the Short-Form Foreign Language Enjoyment Scale, reducing the items to nine for a more efficient measurement (Botes et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it may be frequently noticed by teachers that students complain about disinterest in learning a certain subject, doing homework, participating in classroom activities, or teachers' lectures. In the field of foreign language education and second language acquisition, extant scholarly attempts mainly addressed its sources, measurement, and correlation with other academic emotions (e.g., Dewaele, Botes, & Greiff, 2023;Dewaele, Botes, & Meftah, 2023;Li et al, 2021;Zawodniak et al, 2023), with the context-specific features and differences among varied student groups based on demographic factors such as gender and class type under-researched (e.g., Ma et al, 2023). In addition, a large body of related studies examined EFL or L2 boredom among adult learners such as undergraduate students (e.g., Alanazi & Bensalem, 2024;Bai, 2023;Elahi Shirvan et al, 2023), and little attention has been directed to EFL classroom boredom experienced by students in secondary education (e.g., Y.…”
Section: Introductionmentioning
confidence: 99%